Sharia Law Perspectives on Misrepresentation in the Use of Paylater - Ahmad, Balya Nasim; Sadik (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2024)
There are indications of misrepresentation of the use of paylater which can be a loss for users. This study aims to examine the misrepresentation of unclear billing provisions that cause gharar in practice, regarding the name of the marketing product or paylater feature to consumers, and paylater advertisements that display the beauty to attract users and the impact of not being able to pay. This research is a normative research that is analyzed qualitatively descriptively, an approach to sharia economic law. The findings found that there is an unclear payment bill, even if the user chooses to buy now, pay next month, still be charged an installment fee even though the claim by e-commerce is interest-free. If the user is late in paying every month, a fine will be imposed. All bill nominal has been calculated by the paylater provider when the consumer checks out. When examined in terms of sharia economic law, the practice of the paylater method is the same as that of debt and credit. Buying and selling there is an element of fraud prohibited in Islam. The paylater method is prohibited because it contains elements of usury. On the other hand, there is an opinion that allows Paylater by considering it as aqad ijarah. In Islam, doing business online is allowed as long as there are no elements that are prohibited by sharia. Paylater in its promotion only shows the beautiful side, even though the impact if you can't pay will be a loss for users.